Scientist of Еxtensive Knowledge. On the 70th Anniversary of the Famous Folklorist, Literary critic, Turkologist and Educator – Ibraev Shakimashrip - Auyesbayeva, Пакизат (Turkic Studies Journal, 2021)
-